2006
DOI: 10.1111/j.1439-0418.2006.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Cereal yield losses caused by lepidopterous stemborers at different nitrogen fertilizer rates in Ethiopia

Abstract: Field trials were carried out at three locations in the cool-wet western and one location in the semiarid eastern ecozones of the Amhara State of Ethiopia to determine the effects of nitrogen fertilizer on pest infestation and yield losses caused by lepidopterous stemborers in maize and sorghum. Three N fertilizer levels, i.e. 60, 120 and 180 kg/ ha for maize, and 41, 64, and 87 kg/ha for sorghum, were compared with a zero N treatment. The dominant pest species were the noctuid Busseola fusca (Fuller) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Despite the importance of these crops in the country, yields are very low due to both biotic and abiotic stresses. Among the major biotic constraints are lepidopteran stem borers such as the noctuid Busseola fusca Fuller and the crambid Chilo partellus (Swinhoe), which in outbreak areas cause between 25% and 100% yield loss (Getu et al 2001;Emana and Tsedeke 1990;Gashawbeza and Melaku 1995;Wale et al 2006). In the past, national and international agricultural research institutions have placed major research emphasis on host plant resistance (Ajala et al 2001;Bosque-Pérez et al 1997), biological control Schulthness et al 1997;Zhou et al 2001) and habitat management techniques based on management of soil nutrients (Sétamou et al 1993), trap plants (Ndemah et al 2002) and mixed cropping (Chabi-Olaye et al 2005a;Schultness et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Despite the importance of these crops in the country, yields are very low due to both biotic and abiotic stresses. Among the major biotic constraints are lepidopteran stem borers such as the noctuid Busseola fusca Fuller and the crambid Chilo partellus (Swinhoe), which in outbreak areas cause between 25% and 100% yield loss (Getu et al 2001;Emana and Tsedeke 1990;Gashawbeza and Melaku 1995;Wale et al 2006). In the past, national and international agricultural research institutions have placed major research emphasis on host plant resistance (Ajala et al 2001;Bosque-Pérez et al 1997), biological control Schulthness et al 1997;Zhou et al 2001) and habitat management techniques based on management of soil nutrients (Sétamou et al 1993), trap plants (Ndemah et al 2002) and mixed cropping (Chabi-Olaye et al 2005a;Schultness et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Among the most important biotic constraints to maize production are lepidopteran stemborers such as the noctuid Busseola fusca (Fuller) and the invasive crambid Chilo partellus (Swinhoe) (Polaszek and Khan 1998;Seshu Reddy 1998). Various stemborer control techniques, such as chemical control, botanicals, host plant resistance and cultural control, have been researched and tested Bruce et al 2004;Ali et al 2006;Matama-Kauma et al 2006;Wale et al 2006a;Songa et al 2007). Since the 1990s, both the International Institute of Tropical Agriculture (IITA) in West Africa, and the International Centre of Insect Physiology and Ecology (ICIPE), Nairobi, Kenya, have given increased emphasis on biological control.…”
Section: Introductionmentioning
confidence: 99%
“…Improving soil fertility complements pest control measures (Saroja et al, 1987). Various authors Chabi-Olaye, 2005;Mgoo et al, 2006;Wale et al, 2006a) have shown that nitrogen is associated with the survival of young stemborer larvae and the resulting pest infestation as well as the plants' tolerance to subsequent attacks. Furthermore, reports from western Africa show that the nutritional status of maize affects noctuid borer densities and the ability of the plants to compensate for pest damage.…”
Section: Introductionmentioning
confidence: 99%
“…Until very recently (Wale et al, 2006a), there was no information on the influence of soil nutrients, and especially nitrogen on various trophic levels of the cereal system in Ethiopia. Chemical fertilizers, especially nitrogen, are commonly used in northwestern Ethiopia, but previously it was not known how fertilizers affect stemborer densities in relation to the yields of cereals in these regions.…”
Section: Introductionmentioning
confidence: 99%